Optimization of production and evaluation of Microbial kojic Acid obtained from Sugarcane Molasses (SCM) by Aspergillus sp. - D. E. Mohamed; A. M. Alian; R. M. Mohamed (Пищевые системы)
Kojic acid (KA) is an organic acid that is generated by various fungi, particularly by Aspergillus species, as a secondary metabolite. The current study is aimed to determine the optimal conditions for the production of kojic acid from various fungal strains grown on agro-industrial wastes. After testing six fungal strains for their suitability for kojic acid production, Aspergillus oryzae (AUMC.64) and Aspergillus tamari (AUMC.43) were found to be the highest producers of KA. Three different agro-industrial wastes were screened as a fermentation media and sugar cane molasses showed the highest productivity for (KA). Aspergillus oryzae (AUMC.64), and Aspergillus tamari (AUMC.43) achieved the maximal production of kojic acid (25.91, 18.95 ± 0.001 g. L-1respectively) from sugarcane molasses (SCM) under optimum conditions of growth (10% solution of sugarcane molasses, pH 4.0 and fermentation period of 10 days). Also, the antimicrobial activities of KA produced by A. oryzae AUMC64 and A. tamari AUMC43 against the selected test strains of microorganisms Staphylococcus aureus, Bacillus cereus, Escherichia coli, Salmonella typhimurium were recorded. The maximum growth inhibition zone (20–13.2 mm) was observed on the cultures of Escherichia coli. Meanwhile the antioxidant activities of KA produced by A. oryzae AUMC64 and A. tamari AUMC43 was 79.1 and 62.42%, respectively.